Design and Test Analysis of High Precision Test Bench of RV Reducer Transmission Error - Zhu Zhonggang; Zhang Jing; Zhou Li; Han Yi'nan (Jixie chuandong)
Taking the rotate vector (RV) reducer which is widely used in industrial robot joint as research object, combining with the principle of transmission error measurement, a high-precision encoder is used to build a high-precision test bench, and the data acquisition and processing program is programmed with the help of LabVIEW software. The transmission error measurement tests of imported and domestic reducer are carried out, and the test data is processed by the filtering analysis method, and the result can show the main source of the transmission error of reducer, a reliable reference for the optimization design and manufacturing process improvement of key parts of RV reducer is provided.